Broad-spectrum matrix metalloproteinase inhibition curbs inflammation and liver injury but aggravates experimental liver fibrosis in mice. - Vincent E de Meijer; Deanna Y Sverdlov; Yury Popov; Hau D Le; Jonathan A Meisel; Vânia Nosé; Detlef Schuppan; Mark Puder (PLoS ONE, 2010)
Liver fibrosis is characterized by excessive synthesis of extracellular matrix proteins, which prevails over their enzymatic degradation, primarily by matrix metalloproteinases (MMPs). The effect of pharmacological MMP inhibition on fibrogenesis, however, is largely unexplored. Inflammation is considered a prerequisite and important co-contributor to fibrosis and is, in part, mediated by tumor necrosis factor (TNF)-alpha-converting enzyme (TACE). We hypothesized that treatment with a broad-spectrum MMP and TACE-inhibitor (Marimastat) would ameliorate injury and inflammation, leading to decreased fibrogenesis during repeated hepatotoxin-induced liver injury.Liver fibrosis was induced in mice by repeated carbon tetrachloride (CCl4) administration, during which the mice received either Marimastat or vehicle twice daily. A single dose of CCl4 was administered to investigate acute liver injury in mice pretreated with Marimastat, mice deficient in Mmp9, or mice deficient in both TNF-alpha receptors. Liver injury was quantified by alanine aminotransferase (ALT) levels and confirmed by histology. Hepatic collagen was determined as hydroxyproline, and expression of fibrogenesis and fibrolysis-related transcripts was determined by quantitative reverse-transcription polymerase chain reaction. Marimastat-treated animals demonstrated significantly attenuated liver injury and inflammation but a 25% increase in collagen deposition. Transcripts related to fibrogenesis were significantly less upregulated compared to vehicle-treated animals, while MMP expression and activity analysis revealed efficient pharmacologic MMP-inhibition and decreased fibrolysis following Marimastat treatment. Marimastat pre-treatment significantly attenuated liver injury following acute CCl4-administration, whereas Mmp9 deficient animals demonstrated no protection. Mice deficient in both TNF-alpha receptors exhibited an 80% reduction of serum ALT, confirming the hepatoprotective effects of Marimastat via the TNF-signaling pathway.Inhibition of MMP and TACE activity with Marimastat during chronic CCl4 administration counterbalanced any beneficial anti-inflammatory effect, resulting in a positive balance of collagen deposition. Since effective inhibition of MMPs accelerates fibrosis progression, MMP inhibitors should be used with caution in patients with chronic liver diseases.